Group Counseling with Behavior Contract Technique to Reduce Verbal Aggressiveness Behavior - Jamilludin, Muhammad; Sugiharto, Dwi Yuwono Puji; Japar, Muhammad (Jurnal Bimbingan Konseling)
The aim of this study was to determine the effectiveness of group counseling with behavior contract technique to reduce verbal aggressiveness behavior of MTs students in Kudus Regency. The study used a pre-test post-test one group design. The sample of this study was selected through purposive sampling technique. There were 7 students selected to form a group. They received five times treatment in form of group counseling with behavior contract technique. Meanwhile, the researchers used Wilcoxson analysis to analyze the data. Afterwards, the results of this study proved that group counseling with behavior contract technique effectively reduced verbal aggressive behavior (z = -2.366, p = < 0.05).